PERAN ULAMA PEREMPUAN DALAM PENDIDIKAN ISLAM: UPAYA MENEMBUS PATRIARKI AGAMA DI ERA DIGITAL - Fentika Zahra Qoirunnisa; Arinda Nurmeita Kurniawan; Firda Noor Khalida; Muhammad Afriyanto; Mahmud Yunus Mustofa (Istifkar: Media Transformasi Pendidikan, 2023)
Religious authority is a particular challenge for women ulama because so far this authority has been fully held by male clerics. This paper discusses how female ulama appears on social media and conveys messages of Islamic teachings. In addition, this study also analyzes the phenomenon of religious lectures that are thick with gender nuances on social media delivered by female ulama. This study uses content analysis by analyzing Ning Imas Fiqh Women's content on NU Online YouTube. This article attempts to explain how female ulama penetrates this patriarchal culture by using social media as a medium of da'wah and Islamic teaching. This article argues that today's female ulama are continuously rising from adversity and removing themselves from patriarchal culture. Women ulama present fiqh teachings that are more progressive and interesting. Then this effort is a new step in breaking down the patriarchal culture in Indonesia. Then what about the results of these efforts? This article will answer with research through digital ethnographic methods. The article contains 3 main points. First, review the role and contribution of women ulama in spreading the teachings of fiqh in Indonesia, and second, explore the dynamics of digital da'wah and Islamic teaching analysis of women on the NU Online channel. Third, the efforts of women ulama to penetrate religious patriarchy.